Use of Flow Modeling to Optimize the Twin-Screw Extrusion Process for the Preparation of Lignocellulosic Fiber-Based Composites - Berzin, Françoise; David, Chantal; Vergnes, Bruno (Frontiers in Materials, 2020)
Thermoplastic polymers reinforced by lignocellulosic fibers are increasingly used to replace conventional composites based on carbon or glass fibers. These materials are generally prepared by dispersing the fibers into the polymer matrix by melt mixing in a twin-screw extrusion process. However, during the process, a significant breakage occurs, leading to a reduction in the length and diameter of the fiber. As the mechanical properties of the composite depend, among other, on the fiber morphology, it is important to understand and control the breakage mechanisms during the compounding process. In this paper, we show how the use of a thermomechanical model of twin-screw extrusion coupled with evolution laws of the fiber dimensions makes it possible to calculate the variation in the length and the diameter of the fibers, according to the local values of the flow parameters (shear rate, residence time, temperature, etc.). It is thus possible to define the best processing conditions (screw speed, feed rate, barrel temperature) or the best screw profile to limit fiber degradation and prepare composites with optimal properties.